Self-Directed Learning among Selected Malaysian Women with Breast Cancer - Mansor, Ahmad Zamri (2009)
Breast cancer is the most frequent cancer among Malaysian women. Learning and understanding the disease is important for the women in order to deal with the crisis situation. Self-directed learning is a learning mode that can facilitate a woman with breast cancer in learning and understanding more about the disease. The purpose of this qualitative study was to explore the phenomenon of selfdirected learning among selected Malaysia women with breast cancer. The study is guided by the following research questions: 1. Why did they learn? 2. How did they learn? 3. What challenges did they face in their learning? This qualitative study used in-depth interview technique with ten Malaysian women with breast cancer. Participants were selected using purposeful sampling and snowballing techniques. Interviews were tape-recorded and transcribed verbatim. The validity of data analysis was assured through triangulation, member check, and peer review, and researcher’s bias and assumptions were declared in the study. The findings can be presented in terms of motivation, strategies, and challenges. In terms of motivation, the participants were motivated by the need to confirm information, the need to understand how to deal with their disease, and the need to help the learning of other patients and survivors. Two aspects that emerge under strategies are learning phases and activities. The learning phases involved were coping with the results, seeking information about treatments, preparing for personal life changes, and learning outcomes. The participants used learning activities such as reading Internet articles, books, other printed materials, consulting doctors and asking other survivors. Doctors are generally regarded as the credible learning source. Participants faced two main challenges in their self directed learning, i.e. the emotional effects of exposure to information and the reliability of information. This study presents new understanding of self-directed learning in crisis situations in Malaysian context. This study concluded that self-directed learning of Malaysian women with breast cancer is contextualized by the dimensions of source credibility, cognition, and spirituality.